Corticosteroids A Paradigmatic Drug Class - Pereira, Celso (IntechOpen, 2021)
Corticosteroids have a broad spectrum of mechanisms making them useful for treating a variety of pathological entities. They are crucial drugs in clinical control in a plethora of patients, despite recent advances resulting from the availability of new molecules with great selectivity for different receptors, cells, or biological mediators. This book includes high-quality scientific reviews of corticosteroids and their numerous uses.